An In Vitro Study of the Effects of Methotrexate Loaded Biocomposite Beads on MG63 Osteoblast Cells - A. E. Malash; A. A. Al-esnawy; Khairy T. Ereiba; Ahmed M. Bakr; A. S. Abdraboh (Scientific Reports)
Abstract This study aims to synthesize a new localized drug delivery system of bioglass, polyvinyl alcohol (PVA), cellulose (CNC), and sodium alginate (SA) beads as a carrier for methotrexate (MTX) drugs for the treatment of osteosarcoma. Methotrexate /Bioglass-loaded Polyvinyl/Cellulose/Sodium alginate biocomposite beads were prepared via the dropwise method with different concentrations of (65%SiO2-30%CaO- 5%P2O5) bioglass. Samples were named B0, S0, S1, S2, and S3, respectively. Calcium chloride (CaCl2) was used as a cross-linking agent. The obtained biocomposite beads were investigated by different techniques FTIR, XRD, SEM, etc. The bioactivity of MTX/BG-loaded PVA-CNC-SA biocomposite beads was tested by immersion in simulated body fluid (SBF). The profile release of methotrexate was investigated with UV–vis spectroscopy for 30 days. A cytotoxicity study of the methotrexate was performed by a human osteosarcoma (MG-63) cell line. Results indicated that the formation of a hydroxyapatite layer on the bead’s surface confirmed its biological activity. Bioactivity was directly proportional to the BG content. All samples of B1, S0, S1, S2, and S3 exhibited significant maximum release up to 6 days and were controlled gradually. Cytotoxicity results of biocomposite beads showed that high cell death was detected on the MG-63 cells, with (IC-50 ± SD) of S3 (116.16 ± 1.57) compared with B1 (306.99 ± 2.72) and S1 (204.74 ± 4.55) due to the high release of MTX, which was confirmed by the results of the drug release profile. Results prove that the prepared biocomposite beads can be used as bioactive, drug delivery systems, and anticancer materials.